Physiological characteristics and training practices of mixed martial artists: Considerations for the strength and conditioning coach - Jay, M. (Journal of Australian Strength and Conditioning, 2013)
Mixed Martial Arts (MMA) is a fast paced combat sport where fighters may use any combination of martial art techniques to defeat an opponent. One of the fastest growing sports in the United States, MMA has captured the attention of the sporting world. MMA athletes require highly developed aerobic and anaerobic energy systems, strength, power and flexibility, combined with a blend of striking and grappling disciplines to be successful in the octagon. Due to such high physiological demands, appropriate programming, injury prevention and recovery should be seen as essential elements in a strength and conditioning program to avoid overtraining symptoms. Despite growing popularity, little in the way of peer reviewed scientific research exists on the athletes involved. Greater levels of knowledge are required to ensure the strength and conditioning specialist can best prepare an athlete for a bout. This review examines current literature in MMA and associated striking and grappling disciplines in an attempt to quantify the physiological characteristics and training practices of MMA athletes to best provide general considerations for appropriate program design.